The Mean Vertigo Score (MVS) Outcome Scale and Its Use in Clinical Research for Quantifying Vestibular Disorders - Rahlfs, Volker W.; Zimmermann, Helmuth (Frontiers in Neurology, 2021)
Introduction The Mean Vertigo Score (MVS) is a composite score for defining the burden of disease of patients suffering from vestibular disorders. It has been used in clinical research for about 30 years. This study investigates discriminant validity of the MVS and describes structural relationships of the 12 single criteria used for construction of the MVS. Materials and Methods The statistical analyses are based on the raw data of an earlier conducted randomized, doubleblind, placebo-controlled clinical trial, which compared the following four randomized treatment groups: a fixed combination of cinnarizine and dimenhydrinate (Arlevert), two groups with only one of the two study drugs, and a group with placebo. The method used for the statistical calculations is the Wei-Lachin procedure, a multivariate generalization of the Mann-Whitney test, which takes into account correlations among the 12 single symptoms of the composite score. Results All 12 single symptoms of the composite endpoint proved to be useful for detecting differences (Mann-Whitney effect size measures: 0.58 to 0.73) and thus for discriminating between treatment groups. Their Pearson product-moment correlations are all positive (range 0.07 to 0.71) and point to the same direction, which indicates one-dimensionality and good internal consistency of the composite index MVS. Furthermore, our statistical calculations revealed that successively increasing the number of single items of the MVS to up to twelve enhances its reliability (R12=0.923), which leads to a substantially higher test power and reduction of the number of patients needed (sample size) in a clinical trial. Conclusion The use of the multivariate Wei-Lachin procedure provides further evidence of the validity of the 12-item composite score MVS, based on the efficacy data of its 12 single vertigo symptoms. The present findings demonstrate that the MVS is a powerful tool, which can be used to adequately describe the patients’ self-perceived vertigo complaints, both qualitatively and quantitatively. It may therefore be regarded as a clinically meaningful alternative to other questionnaires that are presently used in vestibular research.